2007
DOI: 10.2220/biomedres.28.191
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessments on the abnormalities of mouse epiphyseal chondrocytes with short term centrifugal loading

Abstract: We have examined the morphological changes in chondrocytes after exposure to experimental hypergravity. Tibial epiphyseal cartilages of 17-days-old mouse fetuses were exposed to centrifugation at 3G for 16 h mimicking hypergravitational environment (experimental group), or subjected to stationary cultures (control group). Centrifugation did not affect the sizes of epiphyseal cartilage, chondrocyte proliferation, type X collagen-positive hypertrophic zone, and the mRNA expressions of parathyroid hormone-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To a certain extent, growing bones are able to align themselves according to the gravity forces exerted upon them, as can be seen in the correction of a mild genu varum in toddlers [17]. However, strong compression inhibits bone growth and tension has an opposite effect by increasing growth in bone length [4, 18]. This is known as the Hueter-Volkman law (Figure 1(b)), which was further defined by Frost in the twentieth century and is often used by clinicians in surgical correction of certain limb deformities [4, 17].…”
Section: Biomechanics Of the Musculoskeletal Systemmentioning
confidence: 99%
“…To a certain extent, growing bones are able to align themselves according to the gravity forces exerted upon them, as can be seen in the correction of a mild genu varum in toddlers [17]. However, strong compression inhibits bone growth and tension has an opposite effect by increasing growth in bone length [4, 18]. This is known as the Hueter-Volkman law (Figure 1(b)), which was further defined by Frost in the twentieth century and is often used by clinicians in surgical correction of certain limb deformities [4, 17].…”
Section: Biomechanics Of the Musculoskeletal Systemmentioning
confidence: 99%
“…However, if external mechanical loading is applied to the growth plate cartilage, the ultrastructural relation between chondrocytes and extracellular fibrils can be dramatically affected and disrupt the chondrocytic columns (12). Therefore, it is important to determine the normal ultrastructure of extracellular cartilaginous fibrils through FIB-SEM observations so that any existing disorders can be readily identified.…”
Section: Introductionmentioning
confidence: 99%
“…The rocket carrying the satellite will generate 80-100 g of acceleration gravity for about 10 minutes in rising stage before to be into the orbit. In 2007 Feritas et al exposed the epiphyseal cartilages of 17-days-old mouse fetuses to centrifugation at 3 g for 16 h mimicking hypergravity environment, and found that the extracellular fibrils, cell shape and cell membranes were disrupted in the centrifuge samples, which indicated that hypergravity disturbs cell-to-matrix interaction in the cartilage model (Freitas et al 2007). In 2003, Sasagawa et al examined the embryonic development of the nematode Caenorhabditis elegans under hypergravity (200 g), the results showed that the embryos after fertilization developed normally whereas the number of eggs laid from an adult hermaphrodite decreased and their hatching rate was reduced under the hypergravity condition (Sasagawa et al 2003).…”
Section: Introductionmentioning
confidence: 99%